Diversity of Nymphalidae in Kedung Banteng Village, Sleman, Yogyakarta - Meylinda, Rachma; Kurniawan, Ardyan Pramudya (Jurnal Biologi Tropis, 2025)
The butterfly family Nymphalidae is a biological treasure with significant environmental value. Butterfly diversity may be seen in places like Kedung Banteng Village in Sleman, Yogyakarta. This study aims to abundance and diversity of Nymphalidae species, as well as environmental parameters in Kedung Banteng Village. Data retrieval using visual encounter survey and exploration. The results of the study found 29 species of Nymphalidae. The most common spesies is Elymnias hipermnestra and Junonia atlites. Diversity index of Nymphalidae in all season were classified as medium category (dry season: 2,42; rainy season: 2,62). Nymphalidae mostly found in air humidity in the dry season is 42.2% ± 3.1%, while in the rainy season is 41.5% ± 3.6%. Light intensity in the dry season is 37,484 lux ± 44,423 lux, while in the rainy season it is 26,517 lux ± 19,310 lux. The dry season wind speed is 0.9 m/s ± 0.7 m/s, while in the rainy season it is 0.5 m/s ± 0.5 m/s and the air temperature is 31.1°C ± 2.3°C in the dry season and 31.5°C ± 1.8°C in the rainy season.